The Narrative of Racism and Violence in Angie Thomas’s The Hate U Give Novel - Rizkana Faridz M; Otong Setiawan Djuharie; Pepen Priyawan (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This research explores the narrative of racism and violence in Angie Thomas’s novel The Hate U Give. Using a qualitative expressive approach, this study analyzes how the author portrays these issues through the novel’s characters, events, and narrative structure. The findings reveal that the narrative of racism and violence is not only depicted through the direct actions of police brutality and social injustice but also through the internal conflicts experienced by the protagonist, Starr Carter. The study shows that the author uses a first-person narrative to convey the complexity of identity, racial discrimination, and resistance against systemic oppression. The narrative not only exposes the physical violence faced by the black community but also highlights the structural violence that reinforces racial inequality. This research contributes to the understanding of how literature can function as a medium to critique social issues and raise awareness about racial discrimination and violence.